Updating of higher education curriculum for future engineers during the COVID-19 pandemic - Galustyan, Olga V.; Zhirkova, Galina P.; Сan, Wang; Gamisonia, Saida S.; Boldyrev, Igor I.; Khripunkova, Olga V. (Journal of Education and Learning (EduLearn), 2024)
Higher education is immersed in unpredictable environments and is facing challenges during the Coronavirus Disease 2019 (COVID-19) pandemic. It needs to adapt to external changes constantly, especially to the level of development of science and technology as the most important component of education courses for future engineers are facing development difficulties within achieving their goals as the core of higher education. Curriculum serves as basis for realization of goals of higher education and curriculum for future engineers needs updating. The paper analyzes dilemma of updating of higher education curriculum for future engineers within its content and structure. During the learning process students participated in curriculum renewal and accelerated the upgrading of curriculum content and structure. Finishing the course, students conducted reflection, improved their understanding during the reflection process continuously that helped them to develop the habit of lifelong learning. The authors propose to expand teaching methods for the courses, to adapt engineering courses to the needs of economic development during the COVID-19 pandemic, to strengthen students’ interaction and participation, to supply multiple participation in curriculum “customization” countermeasures to update higher education curriculum for future engineers.